21st AIAA/CEAS Aeroacoustics Conference 2015
DOI: 10.2514/6.2015-3259
|View full text |Cite
|
Sign up to set email alerts
|

Design of quieter landing gears through lattice-Boltzmann CFD simulations

Abstract: This paper presents a design modification process carried out on a real two-wheel main landing gear configuration driven by a numerical prediction of its aeroacoustic performances. Extensive flow simulations performed using the lattice Boltzmann method are used to explore a wide range of design parameters and different combinations of low-noise devices applied to the inner and outer parts of the wheels. The search of optimal configurations is supported by a deep analysis of the source mechanisms performed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The acoustic response shows that the solid fairing is able to break the shedding mechanism and to deliver with a lower noise footprint that the original configuration. The present result is consistent with what found in previous literature ( [24,34]); however, due to solid surface exposed to the flow, this configuration offers with the maximum loading to the landing structure. Therefore, the usage of porous materials is proposed with the aim to obtain a compromise between the noise-reduction performance and the actual loading on the landing gear structure.…”
Section: Acoustic Response Of Solid and Porous Fairingssupporting
confidence: 93%
See 1 more Smart Citation
“…The acoustic response shows that the solid fairing is able to break the shedding mechanism and to deliver with a lower noise footprint that the original configuration. The present result is consistent with what found in previous literature ( [24,34]); however, due to solid surface exposed to the flow, this configuration offers with the maximum loading to the landing structure. Therefore, the usage of porous materials is proposed with the aim to obtain a compromise between the noise-reduction performance and the actual loading on the landing gear structure.…”
Section: Acoustic Response Of Solid and Porous Fairingssupporting
confidence: 93%
“…An additional way to obtain a similar noise reduction is by adding small, locally mounted solid/perforated fairings [17,18], meshes [19][20][21] or hub caps [22][23][24][25] to landing gear in order to improve the local aerodynamic shape or reduce local velocities, as well as some more advanced concepts such as; optimised bay door design [26], wheel bay treatments [23,27,28] and an upstream solid, retractable flow deflector [29][30][31]. A full review of noise reduction technologies for aircraft landing gear can be found in Zhao et al [32] and a review of bio-inspired aerodynamic noise control in Wang et al [33].…”
Section: A Air Curtain Technology and Permeable Flow Fairingsmentioning
confidence: 99%
“…LBM has recently been validated for a number of aerospace-related applications and, more importantly, it has also been used for a number of applications where it went beyond what was previously possible with CFD. [2][3][4] But despite those successes and the potential to overcome some of the major deficits RANS tools face, there has been one significant limitation for LBM up until recently. The standard LBM scheme, as it was also employed in the commercial LBM solver PowerFLOW ® , is restricted to subsonic Mach numbers.…”
Section: Introductionmentioning
confidence: 99%
“…This module uses an innovative approach based on the dynamics of the flows structures and Alan Powell theoretical work on vortex sound 34 to calculate the noise sources topology and strength. FIND has already been applied in the literature as a noise sources detection tool for HVAC systems noise 35 , wind noise 36 and airframe noise 37 . In this figure, while some noise sources are located near the tip gap area, the major part of the noise sources are clearly located in the wake of the tip gap flow, where the eddy break-up of the merging tip vortices is happening as observed in Figure 10b).…”
Section: Iiid Far-field Noisementioning
confidence: 99%